Plasma Treatment of Polystyrene Films—Effect on Wettability and Surface Interactions with Au Nanoparticles - Islam, Mohammad; Matouk, Zineb; Ouldhamadouche, Nadir; Pireaux, Jean-Jacques; Achour, Amine (Plasma, 2023)
Polystyrene (PS)/Gold (Au) is used for a wide range of applications, including composite nanofibers, catalysis, organic memory devices, and biosensing. In this work, PS films were deposited on silicon substrates via a spin coating technique followed by treatment with argon (Ar) plasma admixed with ammonia (NH3), oxygen (O2), or tetrafluoroethane (C2H2F4). X-Ray photoelectron spectroscopy (XPS) analysis revealed modified surface chemistry for Ar/O2, Ar/NH3, or Ar/C2H2F4 plasma treatment through the incorporation of oxygen, nitrogen, or fluorine groups, respectively. Size-controlled magnetron sputter deposition of Au nanoparticles (NP) onto these plasma-treated PS films was investigated via XPS and AFM techniques. The interaction of the Au NPs, as probed from the XPS and AFM measurements, is discussed by referring to changes in surface chemistry and morphology of the PS after plasma treatment. The results demonstrate the effect of surface chemistry on the interaction of Au NPs with polymer support having different surface functionalities. The XPS results show that significant oxygen surface incorporation resulted from oxygen-containing species in the plasma itself. The surface concentration of O increased from 0.4% for the pristine PS to 4.5 at%, 35.4 at%, and 45.6 at% for the Ar/C2H4F4, Ar/NH3, and Ar/O2, respectively. The water contact angle (WCA) values were noticed to decrease from 98° for the untreated PS to 95°, 37°, and 15° for Ar/C2H2F4, Ar/NH3, and Ar/O2 plasma-modified PS samples, respectively. AFM results demonstrate that surface treatment was also accompanied by surface morphology change. Small Au islands are well dispersed and cover the surface, thus forming a homogeneous, isotropic structure. The reported results are important for exploiting Au NPs use in catalysis and sensing applications.